The analysis of determinants and barriers of household sustainable energy transitions in Tanzania - Rugaimukamu, Kevin Mutayebwa (School of Economics, 2022)
The Tanzanian energy policy is centered around improving access, reliability, and affordability of modern energy services. Up to the year 2018, Tanzania was among a small group of countries that dominated both the top 20 lists of countries in the world with electricity and modern cooking energy access deficits, respectively. The country's electricity access has since increased but the number of households connected to electricity has increased at an uneven rate, with higher connection rates observed in urban areas. Nevertheless, access to modern cooking energy has continued to increase at a very slow rate. The country's household energy use portrays a heavy reliance on wood fuels (charcoal and firewood) for cooking with 90 percent of Tanzanian households using wood fuels for the activity. Nonetheless, it also depicts gradual and modest improvements in households' modern energy use, with regards to electrification and use of modern fuels for cooking particularly in urban areas (LPG and Electricity). This is despite the government's numerous initiatives put in place to spear head the transitions. The implementation of these initiatives has always been delayed and most of the time fallen short of the policy makers expectations, owing to both institutional and policy inefficiencies. This thesis investigates the economics of household energy transition in Tanzania and adds to the literature by looking at the determinants of household adoption of modern cooking fuels (LPG and electricity), looking at the role of social capital in smoothing the adoption of modern cooking fuels. Moreover, we investigate the impacts of these household energy transitions on household welfare indicators, and, lastly, we investigate the institutional challenges in implementing household energy transition initiatives with regards to electrification particularly in rural areas. We do this in three separate but related chapters that form the key components of a thesis constituted of five chapters, with the first and last chapter presenting the introduction and general conclusions of the thesis. The second chapter investigates the determinants of adoption of modern cooking fuels (LPG and electricity) in Tanzania. We model household energy transition to modern cooking fuels with an emphasis on the role of social capital. We utilize membership into key community groups; Savings and Credit Co-Operative Societies (SACCOS) and other self-help groups as a measure of social capital. We make use of three waves of the 2008-2016 Tanzanian panel data set from a nationally representative household panel survey that collects information on a wide range of topics such as agricultural production, non-farm income generating activities, consumption expenditure, and a number of other social-economic characteristics of the households. We employed panel data techniques to ascertain the role of social capital on household energy transitions in Tanzania. For robustness purposes, we ran two regression analyses, one incorporating the social capital variable as a dummy variable and the other as a continuous variable to observe the stability of our results. Moreover, beyond the panel data model specifications, we ran alternative model specifications to check the stability of our results. The third chapter investigates the impacts of household energy transitions on welfare indicators in Tanzania. We conducted two impact analyses, whereby we analyzed the impact of household's use of modern cooking fuels (LPG and electricity) on household welfare indicators (energy expenditure and health) and the impact of household use of electricity on household welfare indicators (energy expenditure, time use, study hours, acute respiratory health). We make use of two national representative data sets, that is the fourth wave of the national panel survey of 2014/15 and the 2015/16 Tanzanian Demographic and Health Survey and the Malaria Indicator Survey to analyze the impacts of household energy transitions on non-health and health related outcomes respectively. We used propensity score matching techniques to ascertain the impact of household energy transitions. We estimated the propensity scores, chose the appropriate matching algorithm to do the matching, assessed the matching quality and performed a sensitivity analysis of the results. The fourth chapter looks at the institutional barriers in implementing household energy transition programs in Tanzania, with an emphasis on rural electrification in Tanzania. We investigate if the political clergy and energy sector governing entities in Tanzania constrain the smooth implementation of rural electrification projects. Moreover, we investigate whether the current rules, laws, and regulations in the electricity supply industry and supporting sectors attract investments in rural electrification projects. Furthermore, we review policies, strategies, and interventions within the energy sector with regards to rural electrification. We use primary data collected from key informants in the sector and augmented this with secondary data from official reports and periodicals from key government and non-government entities in the electricity supply industry sector. We used qualitative data techniques to ascertain the key institutional barriers to rural electrification in Tanzania. The results of chapter two reveal that social capital plays an important role in household energy transitions. Households with membership in self-help groups or Savings and Credit Co-Operative Societies (SACCOS) were more likely to adopt modern cooking fuels (LPG and electricity). Membership in these groups help households raise awareness, gain technical information about, and bridge liquidity constraints on, new technologies including modern energy. Our results remained stable in the different specifications of the social capital variable and econometric models. The results also reveal that household income, household's head age, household size, and availability of biomass stoves and electricity connection to be important determinants of household's adoption of modern cooking fuels. Chapter three results revealed significant impacts of household energy transitions on household welfare indicators. Household use of modern cooking fuels was found to significantly reduce charcoal expenditures, and consequently amount of charcoal used in urban areas. Moreover, the results revealed that use of modern cooking fuels was associated with a reduction of respiratory infection for children under five years old. On the other hand, electrification was found to improve study hours, years of schooling and consequently, schooling outcomes. Moreover, we find suggestive evidence that electrification smoothens information flows and augments social campaigns, thus facilitate promoting issues like family planning. The chapter also reveals an elongation of the working day due to electrification. The results of the fourth chapter show institutional barriers pertaining to non-independence of institutions within the energy sector, deficiencies of the existing policies, strategies and interventions pertaining to rural electrification, the supporting framework's modus operandi not accustomed to serve the electricity supply sector, the uncertainties created by the laws and regulations governing the sector, and the institutional specific challenges such as financial constraints and shortage of staff facing the governing institutions in Tanzania formed some of the key bottlenecks hampering the timely implementation of and achieving of desired outcomes by rural electrification projects in Tanzania as perceived by the stakeholders in the Tanzanian electricity supply industry. The revealed results point to key policy implications, including putting in place policies to enhance the use of modern cooking fuels to cut down the excessive use of charcoal. Furthermore, the government should enhance its efforts not only in increasing access to electricity but also increasing the number of connected households especially in rural areas, so as to reap the associated benefits with regards to schooling, labor and family planning. Thus, raising awareness about modern fuels of energy for cooking through promotions and easing liquidity constraints could go a long way in enhancing the use of modern cooking fuels and increasing households' electricity connections. The best channel to enhance awareness and easing liquidity constraints is community-based groups. The government should promote financial inclusion through community groups to enhance among other things, household energy transitions by easing liquidity constraints. Moreover, encouraging the formation of such groups especially among women could amplify the dissemination of information about modern cooking fuels and heighten diffusion of new technologies, markedly in rural areas. Nevertheless, to smoothen government's implementation of households' energy transition initiatives, institutional barriers must be nullified. The government should review its interventions to make sure they cover all the constraints with regards to hurdles associated with household's energy transitions. Moreover, as the energy sector is a capital-intensive sector, the government should iron out any prohibitive policies, rules, laws, and regulations deterring investments in the sector. One of the polices to advocate for in attracting investment in the electricity supply industry is to push for the use of more renewables. Lastly the government should allow the energy governing entities in the country to exercise their mandate professionally and independently to elicit the desired outcomes. Furthermore, these institutions should be strengthened financially, expertise wise and eliminate bureaucracies in service delivery.